Phytophthora palmivora–Cocoa Interaction - Perrine-Walker, Francine (J Fungi (Basel), 2020)
Phytophthora palmivora (Butler) is an hemibiotrophic oomycete capable of infecting over 200 plant species including one of the most economically important crops, Theobroma cacao L. commonly known as cocoa. It infects many parts of the cocoa plant including the pods, causing black pod rot disease. This review will focus on P. palmivora’s ability to infect a plant host to cause disease. We highlight some current findings in other Phytophthora sp. plant model systems demonstrating how the germ tube, the appressorium and the haustorium enable the plant pathogen to penetrate a plant cell and how they contribute to the disease development in planta. This review explores the molecular exchange between the oomycete and the plant host, and the role of plant immunity during the development of such structures, to understand the infection of cocoa pods by P. palmivora isolates from Papua New Guinea.